The Relationship between Science Literacy Ability and Scientific Attitude with Biology Learning Outcomes through Scientific Approach and Student Retention Class XII MAN Tapanuli Selatan - Ade Apsari Furqon Aritonang; Binary Manurung; Murshid Murshid (BIRCU, 2021)
This study aims to determine: The positive relationship between (1) scientific literacy skills and student learning outcomes (2) scientific attitudes and student learning outcomes (3) scientific literacy skills with student retention (4) scientific attitudes with student retention (5) scientific literacy skills and scientific attitudes with the learning outcomes of students' biology (6) scientific literacy abilities and scientific attitudes and retention of class XII students. This research was conducted at MAN Tapanuli Selatan in 2020. The research method is descriptive linear regression correlational research method with a research sample of 110 students who were determined by total sampling (total sample). The research instrument consisted of a scientific literacy ability test, a questionnaire on students' scientific attitudes, a test of student learning outcomes and retention. The instruments used had been tested for validity, reliability, difference power and degree of difficulty. The research data were analyzed using simple and multiple linear regression analysis techniques using the SPSS 21.0 for windows program. The results showed: There is a positive relationship between (1) scientific literacy skills and student learning outcomes with r2 = 48.6% (2) Scientific attitudes and student learning outcomes with r2 = 11.6% (3) Science literacy skills with student retention r2 = 58.7% (4) Scientific attitude with student retention with r2 = 13.7% (5) Scientific literacy ability and scientific attitude with student learning outcomes with R2 = 49% (6) Scientific literacy skills and attitudes scientific and student retention R2 = 59.2% in class XII MIA MAN Tapanuli Selatan.